The Perception of the Academics and Students Regarding the Entrepreneurial Education Iin Economic Education - Bogdan Gabriel Nistoreanu; Georgica Gheorghe (Amfiteatru Economic Journal, 2014)
The XXI century has brought radical transformations in the ways of organising the society as a whole and particularly of the academic world. It is known that the higher learning institutions have constantly positioned themselves among the sustainable institutions of the civilisation, fact due in large amount to their flexibility, but also to their power of anticipation, transformation, and innovation.
Keywords: I20; I23; I25; C00; 330; academic entrepreneurial education; students; professors; Bucharest University of Economic Studies